A Framework of Contingencies Factors, Government Support and Management Accounting Practices in Malaysian Small and Medium-Sized Enterprises - Nik Herda Nik Abdullah; Nur Maisara Arif Mirza; Shamala Krishnan; Azliza Azrah Mohd Zakaria; Grace Morris (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
Small and medium-sized enterprises (SMEs) are critical in developing countries, as they create significant job opportunities and contribute to global economic development. Numerous Malaysian SMEs are struggling to survive in the aftermath of the COVID-19 outbreak. As a result, the adoption of management accounting practices (MAPs) plays an important role in supporting decision making, which aids in the sustainability of SMEs' economic growth and leads to long-term performance. However, there is limited research on MAPs being used in SMEs across various industries. This paper aims to propose a conceptual framework for the factors affecting MAPs in Malaysian SMEs from a contingency theory perspective. This paper employs a qualitative approach by reviewing all pertinent literature on the subject from various databases and relating it to the current environment, which attempts to bring the entire concept of MAPs into focus based on the findings of previous research and a proposed conceptual framework that can be used for future research. This research has contributed to the literature by providing a conceptual framework for MAPs from the perspective of contingency theory, with an addition on government support, which can improve industry competitiveness, business prosperity, and long-term performance. Based on the proposed framework, further empirical study is needed to examine whether the factors that contribute significantly to the adoption of MAPs in SMEs.